Of Empathy, Imagination and Good Gloves - Schildmeier, Marvin (SCENARIO: Journal for Performative Teaching, Learning, Research, 2016)
From the moment I first stepped in the door to our seminar room I was aware that I was a foreigner here. That was not just due to the fact that I had set out from my familiar Hannover on an Erasmus semester at University College Cork, but rather particularly due to the fact that in choosing the course Drama and Theatre of the 20th and 21st Century, I set foot in hitherto untested territory. As far as theatre and the performing arts were concerned, I was, in fact, a blank page. My stage experience was limited to playing Joseph in the Christmas nativity play, the canon of plays which I had read to those which were a part of the core curriculum in secondary school. I was a foreigner. The mental image of going up on stage made me feel uneasy and at moments when eyes were focused on me, I had the feeling that I could no longer properly control my body language. However, as you must sometimes set yourself new challenges, and as I thought that there could be no better point in time for such a peek outside the box than a semester abroad, in which ...